Contextual Socio-Scientific Issues and Education for Sustainable Development (SSI-ESD) Climate Change Module: Improving Chemical Literacy and Environmental Awareness among High School Students in Ketapang, Indonesia - Ramadanty, Restyani; Handayani, Sri; Putri, Siska Widiana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study investigates the effectiveness of a contextual Socio-Scientific Issues and Education for Sustainable Development (SSI-ESD) learning module on climate change in enhancing students’ chemical literacy and environmental awareness. A quantitative quasi-experimental design was employed, involving 143 tenth-grade students from public secondary schools in Ketapang Regency, Indonesia, assigned to experimental and control groups through class-based random sampling. Data were collected using a validated chemical literacy test and an environmental awareness questionnaire, and analyzed using Multivariate Analysis of Variance (MANOVA). The results revealed significant multivariate and univariate differences between the two groups, favoring the experimental group. The intervention produced a moderate effect size (η² = 0.127), indicating that contextual SSI-ESD learning improved students’ conceptual understanding and pro-environmental attitudes. The module created meaningful connections between abstract chemistry concepts and students’ real-world experiences by integrating local environmental issues such as forest fires and haze. This study provides novel evidence that locally contextualized SSI-ESD modules can strengthen chemistry education in Indonesia while embedding sustainability values, offering implications for curriculum development, teacher training, and education policy.